A mobile technology-based tailored health promotion program for sedentary employees: development and usability study - Yun-Ping Lin; Kwo-Chen Lee; Wei-Fen Ma; Bei-Syuan Syu; Wen-Chun Liao; Hui-Ting Yang; Shu-Hua Lu; OiSaeng Hong (BMC Public Health)
Abstract Background Prolonged sedentary behavior in workplace settings is associated with increased health risks, including chronic diseases and reduced productivity. While various mobile health (mHealth) interventions exist, most focus on single behaviors such as physical activity (PA) or sedentary time, with limited solutions integrating diet, PA, and sedentary behavior for sedentary employees. Objective This study aimed to develop Simple Health, an evidence- and theory-based mHealth web app designed to promote healthy eating, increase PA, and reduce sedentary time among sedentary employees. The study also evaluated the app’s usability. Methods The study followed a two-phase approach. In Phase 1, Simple Health was developed by a multidisciplinary team using social cognitive theory and the ecological model as theoretical foundations. Behavior change techniques such as goal-setting, self-monitoring, and personalized feedback were incorporated. In Phase 2, usability testing was conducted with eight sedentary employees. Participants used Simple Health for five days and completed the mHealth app usability questionnaire (MAUQ) to assess ease of use, interface satisfaction, and perceived usefulness. Open-ended feedback was also collected to identify areas for improvement. Results Most participants (87.5%) found Simple Health easy to use, with usability scores indicating favorable responses across ease of use (mean: 2.20/7), interface satisfaction (mean: 1.91/7), and usefulness (mean: 1.98/7). Participants valued the simplicity of behavior logging and the actionability of personalized advice. Suggestions for improvement included increasing goal-setting flexibility and refining navigation to enhance user experience. Conclusions The development and usability evaluation of Simple Health demonstrate its potential as a workplace mHealth intervention that integrates PA promotion, sedentary behavior reduction, and dietary tracking. While usability feedback was generally positive, refinements such as improved navigation and enhanced goal-setting flexibility could further optimize engagement. Future iterations should explore automatic syncing with wearable devices and expanded implementation in workplace wellness programs to assess long-term adoption and effectiveness.